Ar-40/Ar-39 age of the Lake Saint Martin impact structure (Canada) - unchaining the late Triassic terrestrial impact craters - Schmieder, M.; Jourdan, Fred; Tohver, E.; Cloutis, E. (Elsevier Science BV, 2014)
New 40Ar/39Ar dating of impact-melted K-feldspars and impact melt rock from the ~40 km Lake Saint Martin impact structure in Manitoba, Canada, yielded three plateau ages and one mini-plateau age in agreement with inverse isochron ages for the K-feldspar melt aliquots and a minimum age for a whole-rock impact melt sample. A combination of two plateau ages and one isochron age, with a weighted mean of 227.8±0.9 Ma227.8±0.9 Ma [±1.1 Ma; including all sources of uncertainty] (2σ ; MSWD = 0.52; P=0.59P=0.59), is considered to represent the best-estimate age for the impact. The concordant 40Ar/39Ar ages for the melted K-feldspars, derived from impact melt rocks in the eastern crater moat domain and the partially melted Proterozoic central uplift granite, suggest that the new dates accurately reflect the Lake Saint Martin impact event in the Carnian stage of the Late Triassic. With a relative error of ±0.4% on the 40Ar/39Ar age, the Lake Saint Martin impact structure counts among the most precisely dated impact structures on Earth. The new isotopic age for Lake Saint Martin significantly improves upon earlier Rb/Sr and (U–Th)/He results for this impact structure and contradicts the hypothesis that planet Earth experienced the formation of a giant ‘impact crater chain’ during a major Late Triassic multiple impact event.